ANALYSIS OF VERB TENSES ERRORS OF NON-ENGLISH STUDENTS’ WRITING - Mayaratri, Puspita (Jurnal Bahasa Lingua Scientia, 2020)
Verb tenses errors made by students in writing need more attention from the lecturer in order to prevent them to do another errors. The circumstances that learners do make errors, and these errors can be analysed, carried out a surge of study of learners? errors, called error analysis. The aim of this research was to describe the students? errors and its causes in using verb tenses such as simple present tense, simple present continuous tense and simple past tense in writing composition. This research used error analysis method in a form of descriptive analysis (percentage) with the process as follow: observation, collecting the students? test, analyzing, and interpreting the data. For data collection, essay test was used as the instrument. This research involved 22 students of non-English Department, History of Islamic Civilization Class B of IAIN Tulungagung, as participant. One of the graduate profiles from this department is being a writer so that the skill of writing becomes important for its students. The study traced the most frequent of verb errors fit in the present simple (55.4%), past simple (28.9%), and present continuous (8.43%). Meanwhile, this study described the percentage types of errors called surfaced strategy taxonomy as following: omission (40.4%), addition (23.4%), misinformation (20,2%), and misordering (16%).